Exploring the Relationship Between Diversification, Risk Bank, Size Bank, And Liquidity; Evidence From Conventional Banking In Indonesia - Indraswari, Citra Rahayu; Sari, Kartika; Anggraeni, Puspitasari Wahyu (Economics Department, Faculty of Economic and Islamic Business, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2023)
Banking plays an important role in the economy both micro and macro. In addition, it is crucial for a country to have a strong and robust banking system. To realize a strong and robust banking banks need to maintain their efficiency. Therefore, it is necessary to identify the factors that affect efficiency, including asset diversification, risk, bank size and bank liquidity. The novelty of this research is that there is an asset diversification variable. Asset diversification can protect investors from recurring investment cycles and can save from asset failure. The sample of this research are conventional banks with a total of 10 banks that have the largest share of assets in Indonesia. In this study to identify the effect of asset diversification, bank risk, bank size, and bank liquidity on bank efficiency used multiple linear regression analysis methods were used. This study concludes that asset diversification actually reduces bank efficiency. The increased bank risk, the better efficiency. Then, the size of the bank and liquidity have no effect on efficiency. Therefore, banks need to review the diversification strategy, ensure that the risks associated with each asset and portfolio as a whole are well-identified and look for opportunities to automate repetitive processes and reduce overall operational costs. Through this research, we suggest, (i) Banks need to review the diversification strategy that has been implemented. There may be some areas or types of assets that do not fit the risk profile and objectives of the bank, (ii) Banks need to ensure that the risks associated with each asset and portfolio as a whole are well-identified, measured and managed, (iii) Banks need to look for opportunities to automate repetitive processes and reduce overall operational costs.